Między monografią a koneserstwem. Badania nad polskim dizajnem XX i początków XXI wieku - Korduba, Piotr (Artium Quaestiones, 2021)
The text aims to describe currents, tendencies and fields of interest in design history studies in Poland, which grew in number around the year 2000. There are several characteristic patterns to be observed. First of all, despite the fact that the pioneering monograph on the subject appeared in 1978 (I. Huml), one can still observe terminological diversity, with various terms, such as applied arts and design, being used as synonyms. Secondly, looking at the history of the research, one may draw up a calendar of key events (publications, exhibitions) which led to the development and/or consolidation of the basic vision of Polish design from the end of the 19th century to the beginning of the 21st century, related primarily to the political and artistic history of the country. Thirdly, the increase in historical knowledge on the subject has been generated not only by different environments but also in the context of diverse institutions (academic and museum research, art market, collecting/connoisseurship). Consequently, the research conducted so far has been methodologically diversified, influenced by different goals and results. As a result, in the social reception there is a specific coexistence of projects of a scientific, popular science and commercial nature. A critical point in the dynamics of research was marked by two events which took place at the beginning of the 21st century: the exhibition Rzeczy pospolite and the subsequent publication (2000/2001), and founding of the quarterly “2+3D” (2001). Another marked increase in initiatives has occurred since the end of the 2000s. The demand for knowledge about design history is also, to some extent, animated by the art market. On the one hand, old design collecting generates a spontaneous exchange of messages on social media, while on the other, it stimulates the creation of reliable popular science studies. Research on Polish design has been dominated by the perspective of art history, usually in its traditional version focusing on style as well as the artistic and theoretical context, and highlighting issues of uniqueness and individual authorship, which prevail over functional, technological or social aspects in the discourse. Consequently, there has been no approach that would perceive Polish design and its multiple contexts as a dynamic system, a set of practices and mediations, such as the approach proposed several years ago by Grace Lees-Maffei (Production-Consumption-Mediation Paradigm) for design history. Such a perspective would enhance and stress the importance of research on the relations between various actors in the Polish design community, such as institutions (educational, experimental and research, manufacturing), transmitters (exhibitions, advice) and mediators between production and consumption.